(untitled) (Ágora de Heterodoxias, 2024)
With the exponential growth of information generated through social media and the speed at which these platforms evolve, a significant concern has arisen about how to preserve this information over time. In this regard, this exploratory systematic review seeks to showcase the methodologies used to preserve content available on social media. To this end, an exhaustive search of relevant literature was conducted, selecting 28 studies published between 2012 and 2023; articles (n=20), books (n=4), master’s theses (n=2), academic essays (n=1), and one presentation (n=1). These were synthesized through a matrix developed by the authors, which allowed for the analysis and identification of four main categories: 1) Strategies applied for digital preservation, 2) Systems or mechanisms of digital preservation, 3) Type, format, and support, and 4) Metadata assignment. The results provide a knowledge base; however, criteria such as the implementation of strategies and the standardization of formats require deeper investigation, so this study significantly contributes to the understanding of the complexities involved in the preservation of content on social media and offers a starting point for future research in this constantly evolving field.